MERENCANAKAN STRATEGI PEMBELAJARAN PAI BERBASIS HIGHER ORDER THINGKING SKILL (HOTS) - Andi Nurfadhilah; Anisa; Ahda Khilwa Sabrina; Ahmad wildan; Ahmad Zaki; Nurjannah Nabila Putri Risantri; Sabrun Jamil (STKIP Subang, 2026)
Islamic Religious Education (PAI) is expected not only to improve students' mastery of subject matter but also to develop higher-order thinking skills that enable them to analyze, evaluate, and make decisions based on Islamic values. This challenge requires teachers to design learning strategies that promote active participation, meaningful learning experiences, and student-centered instruction. This study aims to examine learning strategies for Islamic Religious Education based on Higher Order Thinking Skills (HOTS) and to describe their implementation in classroom practice. The research employed a library research method by collecting and analyzing relevant books, scholarly journal articles, and academic documents related to PAI learning strategies and HOTS. The collected data were examined descriptively through data classification, interpretation, and synthesis to obtain a comprehensive understanding of the proposed strategies. The findings indicate that HOTS-based learning can be implemented through well-defined learning objectives, student-centered instructional models, thought-provoking questions that encourage reasoning and analysis, and assessment practices designed to measure higher-order thinking abilities. In conclusion, integrating HOTS into Islamic Religious Education has the potential to improve the quality of learning while fostering students who are critical, creative, reflective, and capable of applying Islamic values in addressing everyday life situations.